The epithelial transcriptome and mucosal microbiota are altered for goats fed with a low-protein diet - Wu, Jian; Tian, Changxin; Jiao, Jinzhen; Yan, Qiongxian; Zhou, Chuanshe; Tan, Zhiliang (Frontiers in Microbiology, 2023)
Feeding low protein (LP) diet to animals impose severe challenge to animals' immune homeostasis. However, limited knowledge about the underlying adaption mechanism of host and ruminal microbiota responding to LP diet were well understood. Herein, this study was performed to examine the changes in relative abundance of ruminal microbiota and host ruminal mucosal transcriptome profiles in response to a LP diet. A total of twenty-four female Xiangdong balck goats with similar weight (20.64 ± 2.40 kg) and age (8 ± 0.3 months) were randomly assigned into two groups, LP (5.52% crude protein containing diet) and Con (10.77% crude protein containing diet) groups. Upon completion of the trial, all goats were slaughtered after a 16-hour fasting period in LiuYang city (N 28°15', E 113°63') in China. HE staining, free amino acids measurement, transcriptome analysis and microbiome analysis were applied to detect the morphology alterations, free amino acids profile alterations and the shift in host ruminal mucosal transcriptome and ruminal microbiota communities. Firstly, the results showed that feeding LP diet to goats decreased the rumen papilla width (P = 0.043), surface area (P = 0.013) and total ruminal free amino acids concentration (P = 0.016).Secondly, microbiome analysis indicated that 9 microbial genera, including Eubacterium and Prevotella, were enriched in LP group while 11 microbial genera, inlcluding Butyrivibrio and Ruminococcus, were enriched in CON group. Finally, in terms of immune-related genes, the expression levels of genes involved in tight junction categories (e.g., MYH11, PPP2R2C, and MYL9) and acquired immunity (e.g., PCP4 and CXCL13) were observed to be upregulated in the LP group when compared to the CON group. Under the LP diet, the rumen exhibited increased relative abundance of pathogenic microbiota and VFA-degrading microbiota, leading to disruptions in immune homeostasis within the host's ruminal mucosa. These findings indicate that the ruminal microbiota interacts with host results in the disruption in animals' immune homeostasis under LP diet challenge.